2020
DOI: 10.1080/01419870.2020.1734220
|View full text |Cite
|
Sign up to set email alerts
|

Why are care workers from the global south disadvantaged? Inequality and discrimination in Swedish elderly care work

Abstract: Using quantitative and qualitative methods, this study investigates inequalities in occupational status and wages between native-born and foreign-born employees in elderly care institutions in Sweden. It finds that employees from Africa, Asia and Latin Americathe "Global South"are disadvantaged in both respects. Combinatory explanations of the inequalities are needed. The shorter work experience of foreign-born workers in the care sector plus the lesser value given to educational credentials obtained outside S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Similar to the findings presented in the theme perceptions on class asymmetries , previous research has shown that the migrant care and domestic sectors are often marked by a high degree of social and economic inequality [ 105 , 106 , 107 , 108 ]. Employers frequently discriminate against and justify paying migrant care and domestic workers low wages based on their gender, ethnicity, social class, religion and nationality [ 89 , 107 , 109 , 110 ].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to the findings presented in the theme perceptions on class asymmetries , previous research has shown that the migrant care and domestic sectors are often marked by a high degree of social and economic inequality [ 105 , 106 , 107 , 108 ]. Employers frequently discriminate against and justify paying migrant care and domestic workers low wages based on their gender, ethnicity, social class, religion and nationality [ 89 , 107 , 109 , 110 ].…”
Section: Discussionsupporting
confidence: 81%
“…Workplace discrimination can have an important impact on the career opportunities of immigrant employees. In a more recent study, using a mixed-methods approach, Behtoui et al (2020) find that discrimination of immigrant workers led to exclusion from more powerful social networks at the workplace, and that immigrant workers thus have less access to valuable resources, leading to drawbacks in both occupational status and wages. These findings are in line with those of Akhavan et al (2007), who showed that immigrants more often report a lack of opportunities in discussing wages and to upgrade their skills.…”
Section: Discrimination and Social Exclusion At The Workplacementioning
confidence: 99%
“…Urban & Slavnic, 2008). They more often tend to be employed in low-skilled jobs (Dunlavy & Rostila, 2013;Ilsøe, 2016;Slavnic & Urban, 2018), generally have lower occupational status (Behtoui et al, 2020), are more often in temporary employment (Akhavan et al, 2007), are more frequently working part-time (Ilsøe, 2016), and are overrepresented in jobs where they work long hours for lower pay in comparison to native-born (Slavnic & Urban, 2018). Some workplace risks in these low-skilled jobs are due to the nature of the job and experienced by people employed in that sector in general, while other risks are uniquely experienced by immigrants and related to their immigrant background.…”
Section: Work-related Physical Psychological and Social Risksmentioning
confidence: 99%
“…Though the evidence is limited, a systematic review by Sterud et al (2018) focused on working conditions and occupational health among immigrants in Europe and Canada concluded that, more often than natives, immigrants experience precarious employment that is negatively correlated with health. Especially non-Western immigrants are more prone to work in low-skilled and lower-paid jobs (Behtoui et al, 2020;Ilsøe, 2016;Slavnic & Urban, 2018) with physical demanding work tasks (Dunlavy and Rostila 2013). Further, work-related factors may have a detrimental effect on health, such as the segregation of lower-educated immigrants into lower-paid jobs with poorer job security and working conditions compared to native workers (Taloyan et al, 2019;Charlesworth & Malone, 2022;Hussein, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the native-immigrant gap in sickness absence is believed to stem from immigrants' disadvantages in their work situations relative to natives. Poor host country human capital, such as language, formal skills, and work-relevant experience, has been put forward as a possible explanation for immigrants' difficulties in entering the labour market (Shields and Price 2002;Chiswick & Miller, 2010) and thus, a selection into low-skilled and physically demanding jobs with less autonomy (Behtoui et al, 2020;Dunlavy and Rostila 2013;Ilsøe, 2016;Shields and Price 2002;Slavnic & Urban, 2018) that adversely affect their health (Sterud et al, 2018). Long-term exposure to demanding and stressful working conditions may affect poor health (Fletcher et al 2011), as theorised in Karasek's (1979) demandcontrol model, which has been used to explain such differences, where demand and lack of control in the work situation cause poor health.…”
Section: Introductionmentioning
confidence: 99%